2020
DOI: 10.3389/fmicb.2020.546230
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Traits of Dihomo-γ-Linolenic Acid Production of the Engineered Aspergillus oryzae by Comparing Mathematical Models

Abstract: Dihomo-γ-linolenic acid (DGLA; C20:3 n-6) is expected to dominate the functional ingredients market for its role in anti-inflammation and anti-proliferation. The DGLA production by the engineered strain of Aspergillus oryzae with overexpressing Pythium 6-desaturase and 6-elongase genes was investigated by manipulating the nutrient and fermentation regimes. Of the nitrogen sources tested, the maximum biomass and DGLA titers were obtained in the cultures using NaNO 3 grown at pH 6.0. For establishing economicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…It is a nonaflatoxin producing strain rendering superior growth performance over other microbial platforms in terms of cell robustness to surrounding environments and existing substrates [2,3]. The accumulative genome datasets of A. oryzae strains (https://www.ncbi.nlm.nih.gov/genome/?term=Aspergillus; accessed on 2 April 2021) have permitted significant progress in both fundamental and applied research [4][5][6][7][8]. Apart from the enzyme, amino acid, and organic acid production, A. oryzae has also been recognized as an oleaginous strain with capability in lipid production [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a nonaflatoxin producing strain rendering superior growth performance over other microbial platforms in terms of cell robustness to surrounding environments and existing substrates [2,3]. The accumulative genome datasets of A. oryzae strains (https://www.ncbi.nlm.nih.gov/genome/?term=Aspergillus; accessed on 2 April 2021) have permitted significant progress in both fundamental and applied research [4][5][6][7][8]. Apart from the enzyme, amino acid, and organic acid production, A. oryzae has also been recognized as an oleaginous strain with capability in lipid production [9].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the enzyme, amino acid, and organic acid production, A. oryzae has also been recognized as an oleaginous strain with capability in lipid production [9]. Several studies demonstrated that A. oryzae has a potential as a cell chassis for production of n-6 polyunsaturated fatty acids (PUFAs) by engineering fatty acid and lipid biosynthetic pathways, thus yielding γ-linolenic and dihomo-γ-linolenic acids [8,10,11].…”
Section: Introductionmentioning
confidence: 99%